2015
DOI: 10.1007/s11356-015-5519-y
|View full text |Cite
|
Sign up to set email alerts
|

Diazinon, an organophosphate pesticide, induces oxidative stress and genotoxicity in cells deriving from large intestine

Abstract: Diazinon (DZ) (O,O-diethyl-O-[2-isopropyl-6-methyl-4-pyrimidinyl]phosphorothioate) is an organophosphate pesticide which is extensively used to control household insects and fruit and vegetable crops. The exposure to this pesticide has been linked to the development of the serious problem in several experimental animals. The contamination of food by DZ may increase its danger to humans. The aim of this study was to investigate the toxic effect of DZ on intestine using an in vitro model (HCT116). Therefore, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 49 publications
2
43
0
1
Order By: Relevance
“…The results showed significantly more ROS in the PbAc, DZN, and PbAc + DZN groups than the control group . According to several authors, both acute and chronic lead and/or cadmium and DZN intoxications were associated with a decreased overall antioxidant capacity in different body organs, including reproductive organs and germ cells …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The results showed significantly more ROS in the PbAc, DZN, and PbAc + DZN groups than the control group . According to several authors, both acute and chronic lead and/or cadmium and DZN intoxications were associated with a decreased overall antioxidant capacity in different body organs, including reproductive organs and germ cells …”
Section: Discussionmentioning
confidence: 90%
“…Once absorbed into the body, DZN becomes bio‐activated to its active oxon metabolites through oxidative desulfuration to oxygen analogues diazoxon, which is even more toxic than DZN . OPs create a diversity of toxicological effects on the nervous, cardiovascular, respiratory, ocular, neurobehavioral, immune, reproductive, placental, and other body systems . Moreover, studies have reported that DZN could increase the formation of reactive oxygen species (ROS), mitochondrial membrane damage, lipid peroxidation, and DNA fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Diazinon (O, O-diethyl O -2-isopropyl -6-methyl pyrimidinyl -4-g-1-phosphorothioate, DZN , as one of organophosphate insecticides, is being used in different agricultural and gardening and could be highly toxic [1]. Contamination of food and water to DZN leads to abnormalities in the function of liver [2], kidney [3], brain [4], intestine [5], heart [6], ovary [7] and testis [8]. DZN decrease testosterone level, sperm count, motility and inhibit spermatogenesis and result in testicular atrophy [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing oxidative stress through mitochondrial dysfunction and immunosuppression can lead to testicular injury and sperm abnormalities [12]. DZN with oxidative stress and generation of free radicals and increment of lipid peroxidation induce DNA fragmentation and apoptosis [5]. Also, Pesticides exposure decrease the endogenous antioxidant levels leading to cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Organophosphorus, carbamate pesticides accounted for more than 70% of the total pesticides amount in China, and have been used worldwide in agriculture (Shi, Lv, & Feng, ). The long‐term intake of fruits and vegetables with over‐standard pesticide residues would cause acute and chronic poisoning, even the risk of cancer (Boussabbeh et al, ). Because of the higher poisonousness, many western countries have set maximum residue limits for pesticides in food (Lefrancq, Jadas‐Hecart, La‐Jeunesse, Landry, & Payraudeau, ).…”
Section: Introductionmentioning
confidence: 99%